2017
DOI: 10.1021/acs.jpclett.7b01516
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic-Mechanical and Dielectric Evidence of Long-Lived Mesoscale Organization in Ionic Liquids

Abstract: Experimental evidence of the dynamics of mesoscopic structure in room-temperature ionic liquids-a feature expected to correlate with many physicochemical properties of these materials-remains limited. Here, we report the observation of slow, sub-α relaxations corresponding to dynamics of nanoscale hydrophobic aggregates in a systematic series of 1-alkyl-3-methylimidazolium-based ionic liquids from detailed analysis of dynamic-mechanical and broad-band dielectric spectra. The emergence of the sub-α relaxations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…The dynamics of CnmimX are also investigated mainly in the context of the non-Stokes-Einstein relation which makes a connection between the microscopic and macroscopic dynamics. Microscopic motions have been investigated by nuclear magnetic resonance (NMR), [46][47][48][49][50][51] quasielastic neutron scattering (QENS), and inelastic x-ray scattering measurements, 8,13,15,[52][53][54][55][56][57][58][59][60][61][62][63] while macroscopically by viscoelastic, 16,46,47,55,58,62,[64][65][66][67][68][69][70][71] dielectric, 49,50,55,[71][72][73][74][75][76][77] and ionic conductivity measurements. 46,47,68,…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of CnmimX are also investigated mainly in the context of the non-Stokes-Einstein relation which makes a connection between the microscopic and macroscopic dynamics. Microscopic motions have been investigated by nuclear magnetic resonance (NMR), [46][47][48][49][50][51] quasielastic neutron scattering (QENS), and inelastic x-ray scattering measurements, 8,13,15,[52][53][54][55][56][57][58][59][60][61][62][63] while macroscopically by viscoelastic, 16,46,47,55,58,62,[64][65][66][67][68][69][70][71] dielectric, 49,50,55,[71][72][73][74][75][76][77] and ionic conductivity measurements. 46,47,68,…”
Section: Introductionmentioning
confidence: 99%
“…[11,[17][18][19][20][21][22][23][24][25][26] Recent studies suggest that the existence and dynamics of the aggregates in neat ionic liquids, associated with fluctuations of the polar and non-polar regions, correlate strongly with many of the physicochemical properties of ionic liquids including transport properties such as zero-shear viscosity, dc ionic conductivity, and static dielectric permittivity. [27][28][29][30][31][32] However, no efforts to exploit the mesoscale organization to design novel ionic liquids with unique physical and chemical properties have been reported. In this work, it is demonstrated that by mixing ionic liquids with varying degrees of solvophobic aggregation, it is feasible to design distinct liquids with macroscopic properties that significantly deviate from weighted contributions of the neat components.The local organization, or morphology, of the mesoscale aggregates is in part determined by the relative volume fractions of the polar and non-polar groups of the component ions.[11] In amphiphilic imidazolium, pyrrolidinium, piperidinium, quaternary phos-…”
mentioning
confidence: 99%
“…An intermediate case occurs in (room-temperature) ionic liquids where mesoscopic scale clustering gives rise to anomalously high liquid viscosities due to the jamming effect. [20][21][22] The mayonnaise effect is also likely to be at play in highly viscous deep eutectic solvents 23 as well as the critical increase in viscosity in liquid mixtures near the liquid-liquid critical point. 24 Similar expressions to Eq.…”
mentioning
confidence: 99%